Puberty Knowledge and Communication among Adolescent Sexual Offenders in Indonesia: A Qualitative Study - Emi kosvianti1, 2 , Emy Susanti3 , Windhu Purnomo4, Agung Suhadi5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Rape against women, as one of sexual assaults form, which has been became a serius issue throughout the world in social and public health. It is a gross violation on the women’s human rights, which is can not be accepted from any perspectives. In the latest cases, the perpetrators of rape are conducted by adolescent or minor. Purpose: This article presents the study how the young sexual offenders’ knowledge on puberty and their sexual communication. Method: This research was qualitative toward 30 sexual perpetrators, all informants are being undergone sentences in Correctional Institutions of Bengkulu province, Indonesia. The informants were all child convicts, (aged less than 18 years) at four correctional institution in Bengkulu province. Results of the study: The perpetrators of sexual assault were middle adolescents who were in-between 16 to 18 years. Based on the results of analysis were found that there were ineffective sexual communication patterns among perpetrators, both informants communication parents, friends, teachers and couples. Moreover, this study found inadequate puberty knowledge among sexual offenders. Research limitations: This article only describes sexual communication and knowledge on puberty, while other individual factors and social aspects are not discussed at all in this article. Originality: Based on the various results of previous studies, there are no researches have been found that specifically examines the behavior of sexual violence by minors in Bengkulu province.